Illegitimate tasks associated with higher cortisol levels among male employees when subjective health is relatively low: an intra-individual analysis - Maria U Kottwitz; Laurenz L Meier; Nicola Jacobshagen; Wolfgang Kälin; Achim Elfering; Jürgen Hennig; Norbert K Semmer (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVES: Illegitimate tasks refer to tasks that do not conform to what can appropriately be expected from an employee. Violating role expectations, they constitute "identity-stressors", as one's professional role tends to become part of one's identity. The current study investigated the impact of illegitimate tasks on salivary cortisol. We analyzed data on an intra-individual level, that is, by examining fluctuations in illegitimate tasks and cortisol within individuals. Furthermore, we investigated the moderating role of perceived health, expecting that illegitimate tasks evoke stronger reactions when perceived health is relatively poor. METHODS: Illegitimate tasks, salivary cortisol, and perceived health were assessed in each of three waves (time lag: 6 months) in a sample of 104 male employees. Data were analyzed by multilevel analysis using group mean centering. RESULTS: Controlling for social stressors, work interruptions, and emotional stability, the experience of more illegitimate tasks was associated with increased cortisol release if personal health resources were low compared to one's mean value of perceived health. Results cannot be explained by inter-individual differences. CONCLUSIONS: This is the first study showing that illegitimate tasks predict a biological indicator of stress, thus confirming and extending previous research on illegitimate tasks. The moderating role of perceived health confirms its importance as a personal resource, implying augmented vulnerability when perceived health is below its usual value. It is plausible to assume that increased stress reactions due to relatively poor health may further weaken available personal resources. Both avoiding illegitimate tasks and restoring personal health seem to be crucial.